Isolated Bacterial Resistance to Antibiotics and Common Pathogens that Cause Neonatal Sepsis - Arooba Idris, Asad Shabbir, Faiqa Nazir, Col.(R) Muhammad Afzal, Asma Yaqub, Anum Rauf (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to record the frequency of isolating organisms causing early-onset neonatal sepsis resistant to common antibiotics, Methodology: This research was a cross-sectional study that was conducted in 2017 and 2018 at the Neonatal Intensive Care Unit of the Benazir Bhutto Hospital in Rawalpindi on 180 children who satisfied the following criteria and were delivered between 34 and 40 weeks of gestation either Spontaneous Vertex Delivery or Cesarean Section. The study was conducted on infants who were born between 34 and 40 weeks of gestation. Those newborns who had congenital defects, had had surgical intervention, had hypoxic ischemic encephalopathy, or had been treated with antibiotics were not included in the research. Every infant had three millilitres of its blood collected and stored in a sterile environment. The blood was placed into the Bactec 9240 blood culture bottles in a direct inoculation. After being transported to the BBH children’s hospital pathology lab, the injection bottles were placed in a Bactee 9240 continuous monitoring blood culture system. The temperature inside the incubator was 37 degrees Celsius. The use of catalase, coagulase, and Dnase in the examination of Gram-positive bacteria was carried out. Using the Kirby-Bauer method, the isolated organism was put through a battery of tests to determine whether or not it was resistant to ampicillin, amikacin, tobramycin, cefotaxime, ceftazidime, ceftriaxone, meropenem, sulbactam, and vancomycin. Meuller Hinton Agar was the medium that was employed. Results: In our study, out of 140 cases, 65.71%(n=92) were between 1-48 hours and 34.29%(n=48) were between 49-72 hours, mean+sd was calculated as 35.96+16.65 hours, 47.86%(n=67) were male and 52.14%(n=73) were females. Frequency of isolated organisms shows that 27.86%(n=39) had S.Aureus, 22.14%(n=31) had E.Coli, 15%(n=21) had Staphylococcus epidermidis, 12.86%(n=18) had Klebseila and 22.14%(n=31) had others. Practical Implication: determination of the isolated bacterial resistance to antibiotics and common pathogens that cause neonatal sepsis would help in the appropriate and effective management of neonatal sepsis in our population Conclusion: Our results reveal that S.Aureus and E.Coli were the common showing 27.86% S.Aureus, 22.14% E.Coli, 15%, Staphylococcus epidermidis, 12.86% Klebseila and 22.14% had others isolates. organisms in EOS cases followed by Staphylococcus epidermidis and Klebseila whereas Ampicillin, Cefotaxime, Ceftriaxon, and Ceftazidime are also resistant in these cases. Keywords: Early onset neonatal sepsis, common pathogens, antimicrobial resistance of isolated organism